Community Service in an Effort to Increase Parental Knowledge and Awareness in Efforts to Prevent Cervical Cancer with HPV Immunization in 2025 - Rina Kartikasari; Irwan Budiono; Innama Sakinah; Etty Nurkhayati; Fera Riswidautami Herwandar; Yunia Khomsati; Lilis Banowati (Civiliza Publishing, 2025)
(1) Background: Cancer is one of the number two deadly diseases in the world after coronary heart. Although it is deadly, the initial symptoms of this disease are never felt by the sufferer, so the patient only comes for treatment when the disease has entered an advanced stage. (2) Purpose of the Study: to increase parental knowledge and awareness about cervical cancer and cervical cancer prevention efforts with HPV immunization (3) Methods: direct observation to measure parents' knowledge and perception of cervical cancer and its prevention efforts with HPV vaccination. The final stage of the activity was a re-evaluation of parents' knowledge and perception of cervical cancer and efforts to prevent it by HPV vaccination using a post test questionnaire (5) Conclusions: increasing knowledge so that awareness arises from parents in efforts to prevent cervical cancer in girls. This activity is expected to increase the number of HPV immunization targets in accordance with the target set by the government.